Transformasi Koperasi Siswa melalui Pendekatan Multiple Intelligences untuk Literasi Kewirausahaan - Darma Sanputra, Adrian Hartanto; Nugraha, Tatas Ridho; Miftakh, Eliza Silviana; Isnaini Putri, Elsa; Orchidta Ramadina, Defrina Eka (Indonesian Journal of Society Engagement, 2025)
This service activity aims to revitalize the function of the SMPN 1 Sumberpucung student cooperative into an active and inclusive means of entrepreneurship learning through the multiple intelligences approach and strengthening the role of young entrepreneur leader. The service was carried out using the participatory action research (PAR) method using the 4P approach: Preparation, Implementation, Closing, and Reporting. This activity involved 50 students and 15 teachers in a series of trainings, business simulations, and organizing an entrepreneurship bazaar. The results of the activities showed a significant increase in students' entrepreneurial literacy, the entrepreneurship bazaar generated a profit of IDR 4,825,000. In addition, the program succeeded in establishing SPENDHUSA entrepreneurial cadres as a driver of student cooperative sustainability. The multiple intelligences approach proved effective in exploring students' entrepreneurial potential according to their dominant intelligence, while supporting the achievement of sustainable development goals (SDGs) point 4 on quality education.